ADMISSION BLOOD GLUCOSE AND BLOOD PRESSURE AS PREDICTORS IN ACUTE ISCHEMIC STROKE: A PROSPECTIVE OBSERVATIONAL STUDY - Dr. Vinoth Khanna Gunasekaran; Dr. Priya Anbarasan; Dr. Sumithra Sampath; Dr. J. B. Ashraf Ali (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Stroke is the leading cause of morbidity and mortality worldwide.(1) Though admission blood pressure and glucose have been individually linked to short-term prognosis after ischemic stroke, their joint relationship with neurological outcome and in-hospital mortality remains incompletely defined in many settings and may be influenced by baseline severity, pre-existing disease, and measurement protocols.Objectives: To evaluate the correlation between blood glucose and blood pressure levels at admission and their impact on the short-term functional outcomes and the mortality among the adults admitted with Acute ischemic stroke. Primary objective: to determine whether admission systolic blood pressure (SBP) and admission blood glucose are independently associated with short-term functional outcome (defined as change in NIHSS between admission and discharge) and in-hospital mortality among adults admitted with acute ischemic stroke.Methods: A prospective observational study was conducted among 100 patients admitted with CT/MRI confirmed acute ischemic stroke at Government Thiruvarur Medical College between May 2021 to May 2022. Demographic, clinical and biochemical data including systolic blood pressure (SBP), diastolic blood pressure (DBP) and blood glucose levels were recorded on admission. Functional outcomes were assessed using the National Institutes of Health Stroke Scale (NIHSS) at discharge. Statistical analysis were performed using IBM SPSS version 26. Descriptive statistics, Mann–Whitney U test, Chi-square test, and Pearson correlation were applied, with p < 0.05 considered statistically significant.Results: Of the 100 patients, 60% were male and the predominant age group was 59–68 years (33%). Elevated SBP, DBP, and blood glucose levels were noted in 62%, 59%, and 69% of the patients, respectively. The mean (± SD) SBP, DBP, and blood glucose were 146.40 ± 38.07 mmHg, 89.50 ± 18.28 mmHg, and 229.88 ± 122.78 mg/dL. Correlation analysis revealed a strong positive correlation between SBP and DBP (r = 0.868, p < 0.001), whereas blood glucose showed weak, non-significant correlations with both SBP (r = 0.069, p = 0.496) and DBP (r = 0.126, p = 0.216). Among the 82 patients assessed for outcome, 46 (56.1%) improved, 23 (28%) remained unchanged, and 13 (15.9%) worsened based on NIHSS scores.Conclusion: Admission hypertension demonstrated a significant association with stroke outcome, whereas hyperglycemia exhibited a weak, non-significant relationship with blood pressure parameters. These findings suggest that hypertension plays a more decisive role than hyperglycemia in influencing the early prognosis in acute ischemic stroke. Early detection and integrated control of both blood pressure and glucose levels are essential for improving short-term outcomes and reducing mortality